Supplementary training for sprinters and hurdlers that isn't supplementary - Thorson, M. (Track Coach, 2020)
Functional training is not supplementary training. It should and can work side-by-side with the traditional strength programs. If coaches understand the biomechanics of function and movement, are creative and innovative, they will be able to blend the two together to implement successful training programs for sprinters and hurdlers that build strength and explosive power.